Human neutrophil activating peptide/interleukin 8 acts as an autoantigen in rheumatoid arthritis. Issue 1 (January 1992) - Peichl, P; Ceska, M; Broell, H; Effenberger, F; Lindley, I J
Abstract : Human neutrophil activating peptide/interleukin 8 (NAP-1/IL-8) has been shown to activate neutrophils to degranulate in vitro and to be a potent chemotactic agonist for neutrophils and lymphocytes in vitro and in vivo. It may therefore be a mediator of inflammatory conditions such as rheumatoid arthritis (RA). Levels of NAP-1/IL-8 were low or undetectable in serum samples from 53 patients with RA. Circulating levels of antibodies to NAP-1/IL-8 showed a strong correlation with the level of quantified C reactive protein and with the number of arthritic joints. These autoantibodies, in a similar manner to quantified C reactive protein, correlated with disease activity and are associated with a lack of clinical improvement when the patient is treated with systemic steroids. This observation indicates an important role for interleukin 8 and its autoantibodies in the inflammatory processes of RA, and may provide a clinically useful marker for the diagnosis of disease severity.